Association of venous thromboembolic events with skin, pulmonary and kidney involvement in ANCA-associated vasculitis: a multinational study. (1st February 2021) - Moiseev, Sergey; Kronbichler, Andreas; Makarov, Egor; Bulanov, Nikolay; Crnogorac, Matija; Direskeneli, Haner; Galesic, Kresimir; Gazel, Ummugulsum; Geetha, Duvuru; Guillevin, Loic; Hrušková, Zdenka; Little, Mark A; et al.
Abstract: Objective: To investigate the occurrence of venous thromboembolic events (VTE) in a large cohort of patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) across the European Union, Turkey, Russia, UK and North America. Methods: Patients with a definite diagnosis of AAV who were followed for at least 3 months and had sufficient documentation were included. Data on VTE, including either deep vein thrombosis or pulmonary embolism, were collected retrospectively from tertiary vasculitis centres. Univariate and multivariate regression models were used to estimate odds ratios (ORs) and 95% CIs. Results: Over a median follow-up of 63 (interquartile range: 29, 101) months, VTE occurred in 278 (9.7%) of 2869 AAV patients with a similar frequency across different countries (from 6.3% to 13.7%), and AAV subtype [granulomatosis with polyangiitis: 9.8% (95% CI: 8.3, 11.6%); microscopic polyangiitis: 9.6% (95% CI: 7.9, 11.4%); and eosinophilic granulomatosis with polyangiitis: 9.8% (95% CI: 7.0, 13.3%)]. Most VTE (65.6%) were reported in the first-year post-diagnosis. Multiple factor logistic regression analysis adjusted for sex and age showed that skin (OR 1.71, 95% CI: 1.01, 2.92), pulmonary (OR 1.78, 95% CI: 1.04, 3.14) and kidney [eGFR 15–60 ml/min/1.73 m 2, OR 2.86 (95% CI: 1.27, 6.47); eGFR <15 ml/min/1.73 m 2, OR 6.71 (95% CI: 2.94, 15.33)] involvement were independent variables associated with a higher occurrence of VTE. Conclusion: Two-thirds of VTE occurred during the initial phase of active disease. We confirmed previous findings from smaller studies that a decrease in kidney function, skin involvement and pulmonary disease are independently associated with VTE.